2001
DOI: 10.1097/00000658-200107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Improved Results of Liver Resection for Hepatocellular Carcinoma on Cirrhosis Give the Procedure Added Value

Abstract: LR represents a well-established therapy for HCC on cirrhosis. It remains one of the fundamentals in the multidisciplinary approach to this tumor and should be considered as the first option for patients with preserved hepatic function and limited disease. Today, LR should offer a surgical death rate of less than 1.5%, a 5-year survival rate of approximately 50%, and a 5-year tumor-free survival rate of 28% when performed in specialized centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
216
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 323 publications
(239 citation statements)
references
References 21 publications
14
216
0
5
Order By: Relevance
“…However, thus far, no randomized trial comparing open and laparoscopic liver resection has been reported. The 5-year survival after resection of HCC is 35-50% in recent large cohort studies [257][258][259]. The long-term survival after hepatic resection depends on tumor characteristics.…”
Section: Liver Resectionmentioning
confidence: 99%
“…However, thus far, no randomized trial comparing open and laparoscopic liver resection has been reported. The 5-year survival after resection of HCC is 35-50% in recent large cohort studies [257][258][259]. The long-term survival after hepatic resection depends on tumor characteristics.…”
Section: Liver Resectionmentioning
confidence: 99%
“…The operative mortality of liver resection has been reduced to less than 5% with some centers approaching to zero mortality in recent years [39,40,56]. The improvement is primarily resulting from advances in surgical techniques, perioperative management, and more cautious patient selection.…”
Section: Outcome Of Liver Resectionmentioning
confidence: 99%
“…12,28 These improved outcomes have resulted from advances in surgery, radiology, and perioperative care and the application of strict criteria for patient selection. Despite a lack of comparative studies, it is possible to recommend hepatic resection for patients with a single HCC lesion if (1) the liver is noncirrhotic or (2) the liver is cirrhotic but hepatocellular function is well maintained, the serum bilirubin level is normal, and the hepatic venous pressure gradient is low.…”
Section: Should Liver Transplantation Be Restricted To a Subgroup Of mentioning
confidence: 99%